Euro in the Slovak Republic - Klučka, Jozef; Strelcová, Stanislava; Leláková, Eva (Univerzita Pardubice, 2009)
The implementation of Euro is linked with risks and opportunities. In the paper is described readiness of the country for the adoption of the common currency – Maastricht criteria.
Keywords: EURO; Maastricht criteria; euro changeover